Dams Change Beta Diversity of Aquatic Communities in the Veredas of the Brazilian Cerrado - Brasil, Leandro Schlemmer; Ferreira, Victor Rennan Santos; Resende, Bethânia Oliveira de; Juen, Leandro; Batista, Joana Darc; Castro, Lourivaldo Amâncio de; Giehl, Nubia França da Silva (Frontiers in Ecology and Evolution, 2021)
The veredas are aquatic environments responsible for supplying most of the water for rivers and streams in the Cerrado. The veredas’ hydromorfic soils retain a large amount of rainwater releasing it slowly during drier periods. Therefore, these habitats are often used to built dams for cattle raising. Here we assessed the environmental conditions and beta-diversity of Odonata and Heteroptera on veredas impacted by dams in the Brazilian Cerrado. We sampled biological communities and a set of environmental variables in 13 veredas, six of which with dams and seven without it. One limnological variable (ORP) and one landscape metric (% of the altered area) differed among veredas with and without dams. These variables were important predictors of both the beta-diversity of Odonata (R2 = 0,754; p <0,001) and Heteroptera (R2 = 0,306; p <0,001). The veredas stand among the most sensitive aquatic environments of the Cerrado. In this study, we show, for the first time, that veredas with dams may lose environmental quality resulting in changes in biological communities, especially ecologically unique species. Because the Cerrado naturally goes through approximately 5 months of severe drought, the veredas are critical for the Cerrado’s hydric safety. Therefore, we recommend that cattle raising activities should rely on artificial water tanks instead of using dams for water storage since it affects ecologically unique species in this poorly known ecosystem.